Analisis Pengaruh Beban Lebih Terhadap Efisiensi Dan Torsi Pada Motor Induksi 3 Fasa - Sartika, Linda; Saputro, Muhamad bahrul Adi; Prasetia, Abdul Muis (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2024)
The 3-phase induction motor is a widely used type of motor in industry due to its cost-effectiveness, compact size, and durability. 3-phase induction motors have several advantages, including high torque and efficiency. However, their performance can be affected by various factors, such as overloading. Overloading can reduce the efficiency of an induction motor. This study aims to analyze the effect of load on the torque and efficiency values of a 3-phase induction motor. The research methodology involved testing the 3-phase induction motor and analyzing the results based on variations in load torque. The results are presented in a Matlab M-file format. The analysis shows that increasing the load affects the torque value, resulting in higher output power and impacting motor efficiency. At 75% load, the motor produces a torque of 1.11 Nm, an output power of 162,8 W, and an efficiency of 41.91%. At 100% load, the motor produces a torque of 1.22 Nm, an output power of 177,7 W, and an efficiency of 38,41%. At 125% load, the motor produced a torque of 1.31 Nm, an output power of 186,0 W, and an efficiency of 35,94%. This study confirms that the optimal load condition for induction motors falls within the range of 75%.